Numerical treatment on a chaos model of fluid flow using new iterative method - Ghosh, Indranil; Chowdhury, Md Sazzad Hossien; Mt Aznam, Suazlan (Semarak Ilmu Publishing, 2022)
This article treats analytically and numerically to the three dimensional Rössler system. The governing equations of the problem are derived from traditional Lorentz system of fluid mechanics to nonlinear ordinary differential equations (ODEs) for modelling. A semi-analytic solution is developed by using New Iterative Method (NIM) whereas the numerical solution is presented by Runge-Kutta order four (RK4) scheme. A comparative studyof the analytical and numerical solutions are made. The results confirm clearly that the two methods coincide closely for both the chaotic and non-chaotic cases of the determined system.This observation would be helpful to apply NIM on nonlinear problemsof fluid flow with different fluid parameters in future.